Where was Ancient Egypt's Kpn(y)? - Lorton, David (1986)
Review article of Alessandra Nibbi, Ancient Egypt and Some Eastern Neighbours (1981), Alessandra Nibbi, Ancient Byblos Reconsidered (1985), Alessandra Nibbi, Wenamun and Alashiya Reconsidered (1985)